Influencia de enmiendas químicas en la recuperación de suelos salinos y sódicos del bosque seco tropical colombiano - González M. Adel E.; Hernández Reyes Rodrigo (Acta Agronómica)
This work was carried out at the greenhouse with de purpose of analyzing the influence of some chemical rectifications on the chemical and agronomic behavior of twelve samples of soils from the Colombian Tropical dry forest; some of these showed high levels of salinity of sodium and magnesium; another organic soil was highley acid-aluminium and magnesium, and other with a very low fertility. The trials were based upon an experimental desing completely at random. Each soil was given three chemical rectifications at two levels or doses, and leaching; a control was just given the leaching. All of the treatments were given two leachings during the essay and two productions of dry matter of sorghum - as the reference plant- were evaluated. At the first essay was proposed to lower until 10 and 5 % of sodium saturation or 20 and 10% of magnesium saturation; in a second essay were applied 50 and 25 t/ha of each chemical rectification; for the third essay the applied doses were 20, 10 and 5 t/ha organic rectifications, such manure and poultry bedding, With the leaching was lowered the salinity in all the soils, below 3 dSm -1; the chemical rectifications, below 4 dS-1; in the majority of the soils. The magnesium and sodium saturation were satisfied in the majority of the treatments using gypsum and sulfuric acid. The pHs were reduced in 95 % in all the soils, but this occurred with most intensity with the sulfuric acid and sulfur than using gypsum. The best physical properties of the soils do not implied that they respond as well in their dry matter productions. Acidic or magnesic soils are best rectified with gypsum. The highest doses of organic rectifications favored the dry matter production. El trabajo se realizó en el invernadero de la Facultad de Ciencias Agropecuarias de Palmira, con 12 suelos del Bosque Seco Tropical Colombiano que presentaban problemas de salinidad, sodio y magnesio; un suelo orgánico fuertemente ácido alumínico-magnésico y otro con muy baja fertilidad. Los ensayos se diseñaron completamente al azar. Cada suelo recibió tres enmiendas químicas en dos niveles o dosis y lavado; el testigo sólo recibió lavado. Todos los tratamientos recibieron dos lavados durante el ensayo y se evaluaron dos producciones de materia seca de sorgo como planta indicadora. En un primer ensayo se propuso rebajar a 10 y 5% de saturación de sodio ó 20 y 10% de saturación de magnesio; en un segundo ensayo se aplicaron 50 y 25 t/ha de cada enmienda química; para el tercer ensayo, las dosis aplicadas fueron de 20, 10 y 5 t/ha de enmiendas orgánicas como gallinaza y estiércol en este caso. Con el solo lavado se logró reducir la salinidad de todos los suelos por debajo de 3 dSm-1; con las enmiendas orgánicas por debajo de 4 dSnf1 en la mayoría de los suelos. La saturación de sodio y de magnesio fueron satisfechos en la mayoría de los tratamientos con yeso y ácido sulfúrico. Los pHs se redujeron en 95 % de todos los suelos pero ocurrió con mayor intensidad con las enmiendas ácido sulfúrico y azufre que con yeso. Las mejores propiedades físicas no implican que los suelos respondan también en sus producciones de materia seca. En suelos ácidos o magnésicos es preferible su recuperación con yeso. La dosis altas de enmiendas orgánicas favorecieron la producción de materia seca.